2009
DOI: 10.1002/pat.1415
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of water‐soluble chitosan and polyvinyl alcohol blend films as potential bone tissue engineering matrix

Abstract: The blend film was prepared by casting solutions of water-soluble hydroxyethyacryl-chitosan (HEA-CS) and polyvinyl alcohol (PVA) and cross-linked by glutaraldehyde. The structure and properties of the blend films were estimated by wide-angle X-ray diffraction (WXRD), contact angle measurements with water, and scanning electron microscopy (SEM). The tensile properties of the blend films were investigated and the tensile strength (TS) and the elongation increased with the increased amount of PVA. The thermal sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Because of its poor water resistance, reasonable crosslink is essential for PVA to reduce the solubility in water. Consequently, PVA has been widely applied in numerous fields, such as food packaging , biomedical applications , and functional film . Especially, various hybrid materials, which were composed of PVA and a serious of reinforcements, have generated extensive interest over the recent years .…”
Section: Introductionmentioning
confidence: 99%
“…Because of its poor water resistance, reasonable crosslink is essential for PVA to reduce the solubility in water. Consequently, PVA has been widely applied in numerous fields, such as food packaging , biomedical applications , and functional film . Especially, various hybrid materials, which were composed of PVA and a serious of reinforcements, have generated extensive interest over the recent years .…”
Section: Introductionmentioning
confidence: 99%
“…On average, twenty measurements were performed per film, which was cut from four different sites. A report demonstrated that the water contact angle of blank chitosan was higher than 83 • due to its hydrophilic nature and high surface tension [76]. In order to decrease the hydrophilicity of chitosan, it was blended with PAH to impart flexibility.…”
Section: Wca Measurementsmentioning
confidence: 99%
“…The bone composition is comprised of organic and inorganic phases and made up of proteoglycans, glycosaminoglycans, glycoprotein collagen, and calcium phosphate [11][12][13][14]. Bone also contains an extraordinary amount of hydroxyapatite (HAp), which has suitable bioactive, biocompatible, and osteoconductive biological behavior.…”
Section: Introductionmentioning
confidence: 99%